THREE-DIMENSIONAL PROJECTIONS OF BRAIN NEOPLASMS IN ONCOLOGICAL SURGERY PLANNING: AN INTEGRATIVE REVIEW (CIPEEX, 2025)
INTRODUCTION: With the advancement of technological sciences, society has begun to question the application of these new instruments in the medical context, revolutionizing studies related to this area, particularly concerning technologies such as stereolithography. OBJECTIVE: To investigate the impact of using three-dimensional projections compared to the absence of these projections on the surgical strategies adopted for patients with brain neoplasms. METHODOLOGY: This is an integrative literature review. After searching the National Library of Medicine (PubMed), Virtual Health Library (BVS), and Google Scholar databases, followed by the application of eligibility and exclusion criteria, 10 articles were included in this study. RESULTS: In most of the assessments used to measure the effectiveness of this practice, the implementation of this model proved positive for potential interventions in different types of tumors—especially in diffuse low-grade gliomas (DLGGs)—whether through questionnaires or quantitative instruments. CONCLUSION: The studies demonstrated significant evolution regarding the use of brain three-dimensional projections, both related to the planning of surgical interventions and to the anatomical understanding of the neoplasms themselves.
Keywords: Brain Neoplasms; Three-Dimensional Projections; Stereolithography; Neurosurgery